2D auxetic metamaterials with tuneable micro-/nanoscale apertures. (September 2020) - Mizzi, Luke; Salvati, Enrico; Spaggiari, Andrea; Tan, Jin-Chong; Korsunsky, Alexander M.
Highlights: A reconfigurable 2D auxetic metamaterial with nanoscale geometric parameters has been manufactured using focused ion beam milling. The metamaterial was loaded in-situ and exhibited an in-plane Poisson's ratio of −0.78 over a 5% strain range. The aperture shape and size undergo large changes with mechanically-induced loading which make it well-suited for use as a tuneable optical metamaterial. Abstract: Modern advanced manufacturing technologies have made possible the tailored design and fabrication of complex nanoscale architectures with anomalous and enhanced properties, including mechanical and optical metamaterials; structured materials which are able to exhibit unusual mechanical and optical properties that are derived from their geometry rather than their intrinsic material properties. In this work, we fabricated for the first time an ultrathin 2D auxetic metamaterial with nanoscale geometric features specifically designed to deform in-plane by using focused-ion-beam milling to introduce patterned nano-slits within a thin membrane. The system was mechanically loaded in-situ and exhibited in-plane dominated deformation up to 5% tensile strain and a Poisson's ratio of −0.78. Furthermore, the porosity and aperture shape of the metamaterial have been shown to change considerably upon the application of strain, with pore dimensions showing a fourfold increase at 5% strain. This mechanically-controlled tuneability makes this metamaterial system an ideal candidate for use as a reconfigurable nano-filter or a nano light-modulator. Graphical Abstract: Image, graphical abstract